Application of an evaluation tool for mega-hospital site sustainability. Assessment of public private partnership large sized healthcare infrastructures in European context. - Brambilla, Andrea; Ergur, Lara; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Healthcare facilities are large and complex infrastructures designed to respond to a growing need of sanitary services in specialized environments to serve an increasing population number while containing costs. New financial and design models emerged for large sized Hospital Facilities (Mega-hospitals) but their site sustainability is questioned. Methods: The paper focuses on a comparison between European region case studies of Public Private Partnership (PPP) Mega-Hospitals. A total of 21 large sized hospitals in operation after 2010 have been compared with the application of the Assessment Tool for Hospital Site Sustainability (ATHOSS). A specific focus on Turkish Hospitals has been also provided as the PPP model is widely adopted in this country. Results: This analysis shows that Turkish cases gets general lower scores than European ones in terms of Construction Density and Community Connectivity (28%;50%), Alternative Transportation (18%; 50%), Site Development (26%; 38%). Connection to Natural World (30%; 52%) and Heat Island Effect (33%; 43%). Only in Development Density criteria (30%; 16%) the score was higher. It also emerged that gross floor area per bed ratio is much larger for Turkish cases (334m2/bed; 198 m2/bed) which can be interpreted as one of the weaknesses related to oversizing such infrastructures. Conclusions: The tool application highlighted some point of attention to be considered when designing and planning Mega-hospital facilities and improvement strategies for site sustainability are suggested.